(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Andrássy, I. 2007. Free-living nematodes of Hungary (Nematoda errantia), II. In: C. Csuzdi & S. Mahunka (Eds.), Pedozoologica Hungarica No. 4. Hungarian Natural History Museum. Budapest, Hungary. 496 pp. [ISBN 963 7093 98 2]